2020
DOI: 10.1186/s12998-020-00318-5
|View full text |Cite
|
Sign up to set email alerts
|

Chiropractic students call for action against unsubstantiated claims

Abstract: Background: The 2019 coronavirus pandemic is a current global health crisis. Many chiropractic institutions, associations, and researchers have stepped up at a time of need. However, a subset of the chiropractic profession has claimed that spinal manipulative therapy (SMT) is clinically effective in improving one's immunity, despite the lack of supporting scientific evidence. These unsubstantiated claims contradict official public health policy reflecting poorly on the profession. The aim of this commentary is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…Chiropractic care has been cautioned about overpromoting the benefits of manipulative treatments in terms of COVID-19 prevention or treatment. Social media claims, in specific on Twitter, suggested that spinal manipulation could boost immunity and help prevent COVID-19, a claim that is unfounded and was called out as such by some in the chiropractic community [48,49]. The Chinese practice of Qigong is less familiar outside China but involves body movement synchronized to breathing combined with meditation.…”
Section: Manipulative and Body-based Methodsmentioning
confidence: 99%
“…Chiropractic care has been cautioned about overpromoting the benefits of manipulative treatments in terms of COVID-19 prevention or treatment. Social media claims, in specific on Twitter, suggested that spinal manipulation could boost immunity and help prevent COVID-19, a claim that is unfounded and was called out as such by some in the chiropractic community [48,49]. The Chinese practice of Qigong is less familiar outside China but involves body movement synchronized to breathing combined with meditation.…”
Section: Manipulative and Body-based Methodsmentioning
confidence: 99%